The Bellmaker : a novel of Redwall - Jacques, Brian (New York : Ace Books, 1996)
Worried about his daughter Mariel, Joseph the Bellmaker is led by a dream from Redwall Abbey to Southsward, where he is caught up in the battle between Squirrelking Gael and the vicious Foxwolf Nagru.
"Ace fantasy."
900
Keywords: Animals -- Fiction; Fantasy; Fantasy fiction